2010
DOI: 10.1039/b916688b
|View full text |Cite
|
Sign up to set email alerts
|

Reformulating time-dependent density functional theory with non-orthogonal localized molecular orbitals

Abstract: Time-dependent density functional theory (TDDFT) has broad application in the study of electronic response, excitation and transport. To extend such application to large and complex systems, we develop a reformulation of TDDFT equations in terms of non-orthogonal localized molecular orbitals (NOLMOs). NOLMO is the most localized representation of electronic degrees of freedom and has been used in ground state calculations. In atomic orbital (AO) representation, the sparsity of NOLMO is transferred to the coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…10,27,39 The ground-state calculations not only demonstrate that NOLMOs are more compact/localized in space than OLMOs but also illustrate that accurate results can be achieved with smaller cutoff radii. Moreover, solution of the time-domain NOLMO-TDDFT equations, with low-scaling effort, was also investigated where NOLMO construction is repeatedly performed to maintain the sparsity of NOLMOs in a system.…”
Section: Introductionmentioning
confidence: 86%
“…10,27,39 The ground-state calculations not only demonstrate that NOLMOs are more compact/localized in space than OLMOs but also illustrate that accurate results can be achieved with smaller cutoff radii. Moreover, solution of the time-domain NOLMO-TDDFT equations, with low-scaling effort, was also investigated where NOLMO construction is repeatedly performed to maintain the sparsity of NOLMOs in a system.…”
Section: Introductionmentioning
confidence: 86%
“…Rewriting Eqs. (16) and (17) in the new non-orthogonal MO representation of Eqs. (20) and 21, one obtains after some rearrangement…”
Section: Lr-tddft With Non-orthogonal Mosmentioning
confidence: 99%
“…Neugebauer and co-workers later extended this method. 14,15 Chen et al 16 developed a linear-scaling TDDFT method using the localized density matrix in an orthogonal AO representation, which Yang et al 17 later extended to use non-orthogonal localized molecular orbitals (LMOs). Liu et al 18 derived LMOs from capped fragment canonical MOs and used them to realize a) herbert@chemistry.ohio-state.edu a linear-scaling TDDFT method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the error in the excitation energies due to the frozen orbital approximation is less than 0.01 eV. 28 proposed an alternative O(N) method for excited states. Instead of the density matrix, time-evolution of LMOs is solved by integrating the corresponding TDKS equation.…”
Section: Linear-scaling Calculations Of the Fock Matrixmentioning
confidence: 99%